Art, Disobedience, and Ethics The Adventure of Pedagogy - Atkinson, Dennis (Education, Psychoanalysis, and Social Transformation, 2018)
This book explores art practice and learning as processes that break new ground, through which new perceptions of self and world emerge. Examining art practice in educational settings where emphasis is placed upon a pragmatics of the 'suddenly possible', Atkinson looks at the issues of ethics, aesthetics, and politics of learning and teaching. These learning encounters drive students beyond the security of established patterns of learning into new and modified modes of thinking, feeling, seeing, and making. .